2022
DOI: 10.1007/s00281-022-00957-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of preterm infants: current evidence and future strategies to individualized approaches

Abstract: Preterm infants are at particularly high risk for infectious diseases. As this vulnerability extends beyond the neonatal period into childhood and adolescence, preterm infants benefit greatly from infection-preventive measures such as immunizations. However, there is an ongoing discussion about vaccine safety and efficacy due to preterm infants’ distinct immunological features. A significant proportion of infants remains un- or under-immunized when discharged from primary hospital stay. Educating health care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 143 publications
1
4
0
Order By: Relevance
“…Thus, gestational and chronological age might be important factors in reducing immunogenicity to HepB, and preterm infants may require an additional dose or early booster vaccination. [26][27][28][29] Previous studies have shown that lower birth weight and smaller gestational age are associated with a decreased immune response after HepB vaccination, 27,30 implying that these factors may also affect the long-term persistence of HepB. Similar results were also observed in the current study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, gestational and chronological age might be important factors in reducing immunogenicity to HepB, and preterm infants may require an additional dose or early booster vaccination. [26][27][28][29] Previous studies have shown that lower birth weight and smaller gestational age are associated with a decreased immune response after HepB vaccination, 27,30 implying that these factors may also affect the long-term persistence of HepB. Similar results were also observed in the current study.…”
Section: Discussionsupporting
confidence: 88%
“…1.1-2.0), and the overall GMC was significantly lower in the PTB exposure group compared to the control group (9.3 vs. 12.4 mIU/ mL). Moreover, Fortmann et al 28 considered that cell-mediated recall responses of preterm infant leukocytes to short HBV exposure were reduced as compared to term infants and dependent on pre-existing antibody levels. Thus, gestational and chronological age might be important factors in reducing immunogenicity to HepB, and preterm infants may require an additional dose or early booster vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extremely preterm infants are born at <28 weeks gestation. Nearly 11% of newborns worldwide are born prematurely each year. , Preterm infants with immature immune systems and low antibody levels are particularly susceptible to infections. Maternal antibody transfer across the placenta begins to increase gradually from the 17th to 18th week of pregnancy, so full-term infants have higher plasma antibody titers than premature infants.…”
Section: Precision Vaccination Using Defined Nanovaccinesmentioning
confidence: 99%
“…The microbiome is often disturbed in preterm born infants, which can increase the risk for tissue inflammation in these children. They emphasize that an improved understanding of tissue-resident immunity holds the potential to unearth novel targets of vaccination and enables individualized approaches to protect preterm born babies in the future [ 2 ] .…”
mentioning
confidence: 99%